Da estrutura frasal à estrutura discursival (Revista de Estudos da Linguagem, 1996)
This artieIe presents a diachronic study ofsecond Ianguage teaching approaches as far as the notion of "structure" is concemed. The study demonstrates that the emphasis on syntatic strocture was a charaeteristic of the grammar-translation, the direet and the stroctural approaches. ln the communicative approach, it is shown, that discourse strocture became the main focus.